Penegakan Hukum dan Keadilan Restoratif dalam Kasus Penggelapan Dana Nasabah: Telaah Putusan No. 107/Pid.B/2022/PN.Pin - Awdina, Hikma; Suryani, Lilis; Putra, Moch. Alfatah Alti (Jurnal Litigasi Amsir, 2024)
This study examines legal considerations and the application of law by judges in Decision No.107/Pid.B/2022/PN. Pin related to the case of falsifying payment documents as a means of embezzlement of customer funds. Using normative research methods, this study analyzes the verdict based on the statements of witnesses and defendants, evidence, indictments, and demands of the public prosecutor. The results of the study show that the criminal act is regulated in Article 374 of the Criminal Code Jo Article 64 Paragraph (1) of the Criminal Code. The defendant, Afri Anjas Situmeang, was found guilty of "Embezzlement committed by a person who controls the goods because there is a continuing employment relationship" and was sentenced to 1 year and 7 months in prison. This research provides insight into the application of the law in cases of embezzlement of customer funds and the judge’s considerations in making decisions.